STUDY OF ELECTRODE LIFESPAN IN SEAWATER ELECTROLYSIS PROCESS TO PRODUCE HYDROGEN GAS - Aziz, Fauzan Abiyyu; Rustana, Cecep E; Fahdiran, Riser (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2022)
This study aims to analyze the effect of the type of electrode in the electrolysis of seawater for the production of hydrogen gas. The methods used include two types of electrodes, namely copper and aluminum and also design tools for electrolysis of seawater. Data collection is carried out every 20 minutes, the electrolysis process takes place at a constant voltage of 12 volts. The results obtained showed that the copper electrode produced 732 ml of hydrogen gas and a lifetime of 820 minutes with an average rate of 0.893 ml/minute and the highest hydrogen yield of 3.83% at 400 to 440 minutes while the aluminum electrode produced 693 ml of hydrogen gas. and a lifetime of 680 minutes with an average rate of 1.019 ml/minute and the highest hydrogen yield of 5.92% at 120 minutes.